Love and Belonging Needs of the Main Character in the Movie "500 Days Of Summer": Psychological Approach - Roy Fernandus Hutauruk; Gaguk Rudianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed to describe and analyze psychological needs from the hierarchy of needs proposed by Abraham Maslow of the main character in the movie "500 days of Summer". This research is descriptive qualitative and the original data from the movie “500 days of Summer” by Scott Neustadter and Michael H. Weber, published in 2009. The researcher used non-participatory observation as a method of collecting data. Moreover, categorization was used to analyze data. The researcher found data on the hierarchy of needs of the main character. The researcher found the data divided into three aspects love and belonging needs, 41 data from intimacy, 35 data from friendship, and that there were no scenes in which the main character interacted with his or her parents, siblings, or biological relatives. Based on The conclusion, the hierarchy of needs was unsatisfied love and belongingness, and the researcher found 76 data of unsatisfied love and belonging needs.